Synthesis And Characterization Of Carbon-Chitosan Composite Electrodes Based On Biomass Carbon Activated Using The Microwave Method - Deden Nurdandi; Herman Aldila; Widodo Budi Kurniawan (Jurnal Riset Fisika Indonesia, 2022)
In this research, the synthesis and characterization of chitosan modified carbon composites based on biomass carbon has been carried out using the microwave method. Chemically activated carbon with 2.5% H3PO4 activator was stirred using a magnetic stirrer for 1 hour and allowed to stand for 24 hours. The carbon was then physically reactivated using a microwave for 20 minutes with a power variation of 800, 1000 and 1200 watts and a Scanning Electron Microscopy (SEM) test was carried out. After the SEM test, chitosan modified carbon was synthesized with a composition ratio of 1:1, 2:1 and 3:1 and the specific capacitance was measured using Galvanostatic Charge-Discharge (GCD) testing. The SEM test results analyzed using ImageJ software-based image processing methods show that the value of sphericity, pore size and carbon porosity decreases with increasing microwave power used. The optimum conditions based on the value of Sphericity, pore size and porosity were obtained at a variation of 800 watts of microwave power with values ​​of 0.952, 0.832 m, and 25.87%, respectively, which were included in the macropore size (>50 nm). Because the higher the power used, the smaller the pore area and porosity. The electrode-specific capacitance values ​​were 3.4 x 10-1 F/g, 24.02 F/g, and 1.3 x 10-1 F/g, respectively. Electrodes with a ratio of 2:1 have the largest capacitance value, because they can be charged by an electric charge. The longer the charge-discharge process, the greater the capacitance value, so the curve will approach a more symmetrical isosceles triangle shape.